Thinking the human from transepistemes in planetary decoloniality-complejity - Rodriguez, Milagros Elena (2024)
The epistemes of human beings enter into crisis with their practice. They make evident their inability to have known each other; while its expeditious complexity is: nature-body-mind-soul-spirit-God. As a research objective, we support transepistemes to think about human beings in planetary decoloniality-complexity. The trans prefix inherits concepts from the legacy of Enrique Dussel. We investigate in the midst of wonderful transmethodologies, in the lines of research titled: planetary decoloniality-complexity in re-linkage; complex transmethodologies and planetary-complex decolonial transmethods. With the transmethod of rhizomatic deconstruction we achieve transepistemes such as: human beings are the creation of God, transepisteme the root of all; the spirit comes from the breath of life of the creation given by God to the clay in Adam; the human being is political, gregarious and he can reform his thinking. Insanity, evil, lack of solidarity are not part of creation, but come from sin; which is incited by humanism, transhumanism and the attack on the nature of creation with the support of artificial intelligence.